Japanese Stiltgrass Control with Herbicides in Cool‐Season Grass Forages. Issue 1 (1st June 2019) - Flessner, Michael L.; Lassiter, Adam; Bamber, Kevin W.
Abstract : Core Ideas: Japanese stiltgrass is an increasingly problematic weed in forages. Japanese stiltgrass can be selectively controlled in cool‐season grass forages. Aminopyralid and aminopyralid + metsulfuron resulted in 68 to 88% control. Glyphosate should be applied after the germination period. Aminocyclopyrachlor is also an option for control, where labeled. Japanese stiltgrass [ Microstegium vimineum (Trin.) A. (Camus)] is an invasive annual grass that is problematic in pastures and hayfields along the United States' Eastern Seaboard. It is particularly aggressive in shaded areas where it outcompetes desirable grasses. Since little research has examined Japanese stiltgrass control in cool‐season grass forages, field studies were conducted in 2015 to 2018 to evaluate various herbicide options labeled for such use. Of the treatments evaluated, only aminopyralid alone and aminopyralid + metsulfuron controlled Japanese stiltgrass (70 to 90%), are registered for use in cool‐season grass forages and are safe to desirable grass species. Weed control was improved when metsulfuron was added to aminopyralid and applied when five to eight true leaves are present (June in this study) but not earlier than when one to five true leaves are present (May in this study). Other effective treatments for control included glyphosate alone or with pendimethalin and aminocyclopyrachlor. Studies suggest that applying glyphosate shortly after the germination period ceases (June in this study) results in better control than earlier in the season (May in this study). Application timing should be carefully considered.